Transitional politics: Emerging incentive-based instruments in environmental regulation - Toke S. Aidt; Jayasri Dutta (Fondazione Eni Enrico Mattei (FEEM), 2001)
In the past 15 years, incentive-based environmental policy instruments, such as pollution taxes and tradeable pollution permits, have become an important supplement to tradition command-and-control instruments in Europe and the U.S. This paper proposes a positive theory of environmental instrument choice that can be used to explain this trend. We imagine a democratic society that seeks to lower the level of pollution from industrial production to a pre-specified target. The target can be implemented by one of three instruments: [Q]: quantity controls; [P]: tradeable permits; and [T]: pollution taxes. We characterize political equilibrium as an evolving policy compromise between special-interests, representing polluters, and the electorate. We identify three factors that play a key role in explaining the recent trend in instrument choice: increasingly ambitious environmental targets, learning-by-doing driven reductions in transaction costs associated with permit trading, and (abatement) cost-reducing technological progress.
Keywords: D78; H23; Q28; 330; Instrument choice; political economy; environmental policy; Umweltpolitik; Umweltstandard; Ökosteuer; Emissionshandel; Neue politische Ökonomie; Theorie